How reliable are forensic evaluations of legal sanity? - Gowensmith, W Neil; Murrie, Daniel C; Boccaccini, Marcus T (Law and human behavior, 2013)
When different clinicians evaluate the same criminal defendant's legal sanity, do they reach the same conclusion? Because Hawaii law requires multiple, independent evaluations when questions about legal sanity arise, Hawaii allows for the first contemporary study of the reliability of legal sanity opinions in routine practice in the United States. We examined 483 evaluation reports, addressing 165 criminal defendants, in which up to three forensic psychiatrists or psychologists offered independent opinions on a defendant's legal sanity. Evaluators reached unanimous agreement regarding legal sanity in only 55.1% of cases. Evaluators tended to disagree more often when a defendant was under the influence of drugs or alcohol at the time of the offense. But evaluators tended to agree more often when they agreed about diagnosing a psychotic disorder, or when the defendant had been psychiatrically hospitalized shortly before the offense. In court, judges followed the majority opinion among evaluators in 91% of cases. But when judges disagreed with the majority opinion, they usually did so to find defendants legally sane, rather than insane. Overall, this study indicates that reliability among practicing forensic evaluators addressing legal sanity may be poorer than the field has tended to assume. Although agreement appears more likely in some cases than others, the frequent disagreements suggest a need for improved training and practice.